MMZ: A Study on the Implementation of Mathematical Game-based Learning Tool - Nur Syaheera, Sulaiman; Hamzah Asyrani, Sulaiman; Nor Saradatul Akmar, Zulkifli; Tuty Asmawaty, Abdul Kadir (The Science and Information (SAI) Organization Limited, 2023)
Mathematic has always been one of the hardest subject to be learnt during school. This is the very same issue that student have been facing no matter the level of education that they are in, and this is the reason why Math Maze Zone or also known as MMZ had been developed. MMZ is a mathematical game-based learning tool for primary school students to help them prepare for their final examination for the mathematics subject. The proposed game will consist of mathematical questions and the game design will be focusing on a maze where user will have to search for a way out from the maze while going through the checkpoint within the maze. The checkpoint will consist of mathematical questions and when user answered correctly, they will be able to continue their journey to explore the maze. MMZ focused on 1 chapter only for now which is Chapter 8: Space and Shape. Although the game only consists of one-chapter, primary school students can play the game to enhance their knowledge and to help them to be more engaged with mathematics subject by playing the game. The results will be taken from the perspective of adult who have close relationship with standard six students. Five main sections will also be identified along with MMZ to ensure getting a good result.